A common name for the bat family Rhinonycteridae—the Trident Bats - Armstrong, Kyle N.; Goodman, Steven M.; Benda, Petr; Hand, Suzanne J. (Zootaxa, 2016)
Recent elevation in the rank of J.E. Gray’s (1866) ‘Leaf-nosed Bats’ the Rhinonycterina to family level recognised the phylogenetic uniqueness of bats in the extant genera Cloeotis, Paratriaenops, Rhinonicteris and Triaenops, and the fossil genera Brachipposideros and Brevipalatus (Foley et al. 2015). In the systematic summary of that paper, attention was drawn to the issue of correct nomenclature because of past ambiguity around the appropriate spelling of the type genus Rhinonicteris (see also Simmons 2005; Armstrong 2006). However, no suggestion was made for the common name of the Rhinonycteridae, and that used for the Hipposideridae was simply duplicated—‘Old World Leaf-nosed Bats’. It would be helpful for this newly distinguished family to have its own appellation—to avoid unnecessary confusion in the wider literature, and to recognise its distinctiveness and evolutionary history.